Functions and Strategies to the Integration of Multicultural Values in Textbook Discourse for Elementary School Students - Sultan, Sultan; Haris, Hasnawi; Anshari, Anshari (Lingua Cultura, 2020)
This research was designed to reveal two crucial issues in multicultural education, namely functions and strategies to the integration of multicultural values in textbook discourse. Content analysis was employed in this research to generate systematic and objective findings. Data were collected from textbooks used by the fourth-grade students in Indonesia and published by the Ministry of Education and Culture, Republic of Indonesia. Data collection was performed using the read-and-quote technique. Data analysis consisted of identification, categorization, and interpretation. The results of the analysis reveal that (1) multicultural values represented in textbook discourse function to build students’ positive attitude towards individual, cultural, ethnic, and gender differences to instill an anti-discrimination attitude towards different ethnics, religions, races, and develop students’ pride in sociocultural diversity. (2) Multicultural values are internalized through fiction, story characterization, cultural products, songs, and ethnic philosophies. Sociocultural aspects, social problems, and characteristics of the students are identified as factors that may impact on the functions and strategies to the internalization of the multicultural values.